Mining for salt-tolerant genes from halophyte Zoysia matrella using FOX system and functional analysis of ZmGnTL - Zheng, Yuying; Zong, Junqin; Liu, Jun; Wang, Ruying; Chen, Jingbo; Guo, Hailin; Kong, Weiyi; Liu, Jianxiu; Chen, Yu (Frontiers in Plant Science, 2022)
Zoysia matrella is a salt-tolerant turfgrass grown in areas with high soil salinity or effluent water. Previous studies focused on explaining the regulatory mechanism of Z. matrella salt-tolerance at phenotypic and physiological levels. However, the molecular mechanism associated with salt tolerance of Z. matrella remained unclear. In this study, a high-efficient method named FOX (full-length cDNA overexpression) hunting system was used to search for salt-tolerant genes in Z. matrella. Eleven candidate genes, including several known or novel salt-tolerant genes involved in different metabolism pathways, were identified. These genes exhibited inducible expression under salt stress condition. Furthermore, a novel salt-inducible candidate gene ZmGnTL was transformed into Arabidopsis for functional analysis. ZmGnTL improved salt-tolerance through regulating ion homeostasis, reactive oxygen species scavenging, and osmotic adjustment. In summary, we demonstrated that FOX is a reliable system for discovering novel genes relevant to salt tolerance and several candidate genes were identified from Zoysia matrella that can assist molecular breeding for plant salt-tolerance improvement.